Nanovlakna za dostavo učinkovin in tkivno inženirstvo - Zidar, Anže (Farmacevtski vestnik, 2021)
Nanofibers provide unique systems for drug delivery and tissue engineering. In recent years, major advances have been made towards the formulation of innovative medicines and tissue replacements for the treatment of disease and injury. Nanofibers are made by electrospinning of natural and/or synthetic polymers, and as such, they can have a range of different compositions and structures (e.g., monolayers, multilayers, 'sandwich'). They also show unique combinations of structural, functional and mechanical properties. This flexibility has led to the development of a wide assortment of nanofibers as drug-delivery systems and tissue-regeneration structures. This review covers the preparation of nanofibers by electrospinning and provides the details on their release kinetics for small molecules and biopharmaceuticals, and their use for treatment and tissue engineering. Polymeric nanofibers in tissue engineering support proliferation and growth of cells, hence encouraging tissue regeneration. Despite the many advantages of nanofibers, they are not yet in clinical use. This is mainly due to insufficient data on their safety and limitations in their industrial production, but these aspects are expected to be overcome soon.
Keywords: Dostavni sistemi; elektrostatsko sukanje; Nanotehnologija; nanovlakna; Polimeri; sproščanje učinkovin; Tkivno inženirstvo